Stakeholders’ Mapping Based on Cultures In Coastal Area of Surabaya - Ekowanti, Mas Roro Lilik; Raharja, Wildan Taufik (European Publisher, 2019)
Surabaya City is the biggest city in the province of East Java. Not only physical development, but social, economic and human resource sector are also developed. There are disparity in development in the SurabayaCity, especially in north coastal area of Surabaya in which the majority of people have low income. The problem is that many people refused to follow the programs. The Government of Surabaya must find a new approach to intervene the implementation of development programs.This research aims to map stakeholders based on cultures that have a significant influence on development and identify relevant stakeholders who have roles in the development. The research method used a qualitative approach with case studies in which researchers investigate carefully, event, program, process activity, or group of individuals. Techniques to determine informants used purposive and snowball techniques. The study used triangulation method for checking the validity of data and used 6 stages of qualitative research data analysis approaches. The result of the study shows that religious stakeholders are the dominant factor for intervening the government program implementation. The future research shall discuss about how to intervene a policy with cultural stakeholders mapping approach in improving the program of development and community welfare in the Surabaya City.